Національна ідентичність: особливості формування - Макаренко, Н.Ю. (Збірник наукових праць "Політологічні студії", 2010)
У статті розглядаються особливості формування української національної ідентичності, аналізуються ментальні, світоглядні відмінності між західноукраїнською, південноукраїнською та східноукраїнською субкультурами. In this article we are talking about conditions of national identity forming, historical and geopolitical circumstance witch provide it regional character. In historical view we are talking about outside and inside factors, there influence become a differentiation in national identity of the Ukraine citizens.